2020
DOI: 10.1002/ajoc.202000160
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Sulfenamides through Mitsunobu‐type Coupling Reaction of Thiols with Amines using Dibenzyl Azodicarboxylate

Abstract: SÀ H activation reaction of thiols employing dibenzyl azodicarboxylate (DBAD) has been developed for the preparation of sulfenamides. The dehydrogenation of thiols and amines under these reaction conditions involved the formation of dibenzyl hydrazine-1,2-dicarboxylate (5 a), which led to the SÀ N bond formation reaction. The reaction proceeds efficiently with the release of 5 a and affords various sulfenamides in good to excellent yields.[a] S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Considering sustainability and to satisfy some principles of green chemistry, the direct coupling of thiols with amines for sulfenamides and disulfides is expected be a better choice. Recent developments mainly include the use of pressurized oxygen as an ultragreen oxidant under the influence of 2,2,6,6-(tetramethylpiperidin-1yl)oxyl (TEMPO) (Yang et al 2017), the complex metal catalyst cobalt-phthalocyanine Co(phcy)(SO3Na)4 under heated conditions (Dou et al 2017), Mitsunobu-type coupling using dibenzyl azodicarboxylate (DBAD) as the oxidant (Ryu et al 2020), electrochemical dehydrogenative coupling pathways with excess Bu4N•BF4 (Tang et al 2019) or a combination of tetrabutylammonium perchlorate (TBAClO4) and HCl (Laudadio et al 2017) or toxic LiClO4 (Yang et al 2018) as the electrolyte to facilitate the oxidation process. Nevertheless, the use of (excess) toxic reagents/electrolytes, complex heavy metal catalysts, acidic additives (requiring neutralization before draining, leading to waste salt stream formation), strong oxidants, or explosive electrolytes might cause environmental concerns, and for those employing pressurized O2, ) special pressurized vessels are required to prevent possible chemical production accidents (Shinkar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Considering sustainability and to satisfy some principles of green chemistry, the direct coupling of thiols with amines for sulfenamides and disulfides is expected be a better choice. Recent developments mainly include the use of pressurized oxygen as an ultragreen oxidant under the influence of 2,2,6,6-(tetramethylpiperidin-1yl)oxyl (TEMPO) (Yang et al 2017), the complex metal catalyst cobalt-phthalocyanine Co(phcy)(SO3Na)4 under heated conditions (Dou et al 2017), Mitsunobu-type coupling using dibenzyl azodicarboxylate (DBAD) as the oxidant (Ryu et al 2020), electrochemical dehydrogenative coupling pathways with excess Bu4N•BF4 (Tang et al 2019) or a combination of tetrabutylammonium perchlorate (TBAClO4) and HCl (Laudadio et al 2017) or toxic LiClO4 (Yang et al 2018) as the electrolyte to facilitate the oxidation process. Nevertheless, the use of (excess) toxic reagents/electrolytes, complex heavy metal catalysts, acidic additives (requiring neutralization before draining, leading to waste salt stream formation), strong oxidants, or explosive electrolytes might cause environmental concerns, and for those employing pressurized O2, ) special pressurized vessels are required to prevent possible chemical production accidents (Shinkar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the group of Ko also synthesized a library of 2-benzothiazolesulfenamides (11 examples; 42–96% yield) in a similar manner employing dibenzyl azodicarboxylate (DBAD) as a promoter under ambient conditions. 31 Similarly, 2-mercaptobenzoxazole was also compatible and reacted well with the same set of amines to give the corresponding 2-benzoxazolesulfenamides with slightly diminished yields as compared with the 2-mercaptobenzothiazole.…”
Section: Synthesis Of Sulfenamidesmentioning
confidence: 92%
“…Ko et al have reported SÀ H activation of thiols in a novel way for construction of SÀ N bond using DBAD. [47] After optimizing the reaction conditions, a variety of sulfenamides were synthesized through coupling between thiols (1 equiv) and amines (6 equiv) in presence of DBAD (1.5 equiv) (Scheme 36). Both acyclic and cyclic amines gave excellent results in terms of isolated product yield, irrespective to the size of cyclic ring of amine.…”
Section: Sà N Bond Forming Reactionsmentioning
confidence: 99%
“…Ko et al . have reported S−H activation of thiols in a novel way for construction of S−N bond using DBAD [47] . After optimizing the reaction conditions, a variety of sulfenamides were synthesized through coupling between thiols (1 equiv) and amines (6 equiv) in presence of DBAD (1.5 equiv) (Scheme 36).…”
Section: S−n Bond Forming Reactionsmentioning
confidence: 99%